Strategic leadership and strategy implementation in commercial banks in Kenya - Habil Olaka; Peter Lewa; Peter Kiriri (Kenya Bankers Association (KBA), 2018)
Purpose: The general objective of this study was to investigate the influence of strategic leadership on the implementation of strategy in the commercial banks in Kenya. The seven critical components of strategic leadership studied were strategic direction, core competencies, human capital, social capital, corporate culture, ethical practices and strategic controls. More specifically, the study investigated the influence of these components on the implementation of strategy in the commercial banks in Kenya. Methodology: Adopted a quantitative research design whose target population was the top management team in the commercial banks in Kenya. The instrument of data collection was tested for reliability using the Cronbach alpha test and for validity using the KMO and Bartlett's test. Statistical analysis was then carried out on the data collected. Findings: The study finds that there is a positive statistically significant relationship between effective implementation of strategy with only two of the strategic leadership actions which are 'determining strategic direction' and 'establishing balanced organization controls'. The study recommends that the leadership and in particular the CEO to focus his energies on providing the strategic direction of the organization if it is to achieve its strategic objectives of remaining competitive in the market. Similarly establishing a balance between strategic and financial controls has a direct influence on the implementation of strategy. A strategic leader creates wealth by striking a balance between the constraining influence of financial controls and the long term focus of the strategic controls.
Keywords: 330; strategic leadership; strategy implementation; strategic direction; resource portfolio; organisational culture; ethical practices; organisational controls